Study on Status of Fish Diseases in Nepal - Shrestha, S. P.; Bajracharya, P.; Rayamajhi, A; Shrestha, S. P. (Nepalese Veterinary Journal, 2019)
Fisheries play an important role in increasing the Nepalese economy as well as sustaining livelihood of some ethnic groups of our country. With the increased demand of fish, pisciculture have also increased to a great extend. Due to the rise in fish culture, there has been also rise in fish diseases. The study aims to investigate different parasitic, bacterial, fungal diseases in fish and to suggest treatment to control the diseases in four different fish farm of Nepal. A cross- sectional qualitative method was used to collect data from four selected fish farm (Kakani, Trishuli, Begnas, Mirmi) of Nepal. Infected fishes were transferred to the lab in oxygen filled plastic bags and further tested for bacterial, fungal and parasitic infection. The result of the study indicates that Epizootic Ulcerative Syndrome was the most common bacterial-fungal disease that had a significant impact on common carp fish especially in Trishuli, Begnas and Mirmi. Coccidiosis caused by Eimeria spp was found to be a growing problem in rainbow trout farming (Kakani, Nuwakot) infecting intestine, liver, gut and skin causing yellow diarrhea and skin lesions. Trichodina was observed number one problematic parasitic in carp culture not only in government farm like Begnas and Mirmi, but also in commercial farms in most of the fishery areas of the country. Fin rot were more commonly reported during winter months affecting common carp, Silver carp, Bighead carp, Fingerling Fish causing fin erosion in them. Ascites in brood fishes (Trishuli) was noticed which may be due to bacterial infection and due to nutritional deficiency. Besides this, white spot in the gills (a protozoan parasitic disease) was perceived and to control it Neodox with Formalin (150ppm) was used and was found to be very effective. This study also identified some fish health management related problems in fish farms of Nepal such as lack of assistance, poor technical knowledge, and lack of suitable diagnostic laboratory and their proper use.